PENGARUH STRES KERJA TERHADAP KEPUASAN KERJA PEGAWAI - Gofur, Abdul (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2018)
The purpose of this study was to determine the effect of work stress on employee job satisfaction in one of the Directorate in the State Ministry. In this study used associative research methods using a quantitative approach. The population in this study were employees in one of the Directorate in the State Ministry, with a sample of 30 people with data collection techniques through questionnaires and literature study. Data analysis techniques using simple regression through SPSS version 23. The findings of this study that there is a significant influence between work stress on job satisfaction, where both variables have a strong and positive correlation. The magnitude of the effect of work stress on job satisfaction is 86.2%. Keywords: Job Stress, Job Satisfaction